2012
DOI: 10.1159/000346325
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Obesity among Mexican Adults

Abstract: Objectives: To quantify the access to diagnosis and treatment of obesity and intentional weight loss among obese adults in Mexico and to identify the sociodemographic factors related to these events. Methods: The 2006 Mexican National Health and Nutrition Survey – representative of the adults aged 20 to 64 years – was analyzed. Whether people had received diagnosis and treatment from health professionals and whether they had intentional weight loss were explored. The independent variables were: sex, age, socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In Mexico, the issue of obesity is alarming because of its high prevalence 1 ; however, only a small fraction of the population goes to professional health services for diagnosis and treatment 32 . Pérez-Salgado et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, the issue of obesity is alarming because of its high prevalence 1 ; however, only a small fraction of the population goes to professional health services for diagnosis and treatment 32 . Pérez-Salgado et al .…”
Section: Discussionmentioning
confidence: 99%
“…Pérez-Salgado et al . suggest that this could be because the government institutions in Mexico focus mainly on raising awareness among the population about diseases that derive from obesity 32 and, therefore, research focused on improving the effectiveness of treatments is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that obesity has been declared the “main modifiable risk factor in the country”,7 the latest published data on diagnosis from the Mexican health and nutrition survey showed that only 20% of adults suffering from obesity have been diagnosed by a health care provider 8. The under-diagnosis of obesity is well known, even in developed countries such as the United States 9.…”
Section: Obesity Is Under-diagnosed In Mexicomentioning
confidence: 99%
“…In relation to obesity management, national-level data revealed that only 8% of individuals with obesity had received treatment by a health care provider 8. However, there is some evidence that a significant proportion of adults may be trying to lose weight, including with strategies that have limited or no scientific support such as herbal products and dietary supplements 16.…”
Section: Obesity Is Under-treated In Mexican Adults and The Treatmentmentioning
confidence: 99%
“…Related to the above, Mexican authorities seem to be aware that COVID-19 represents a big challenge given the health status of the population and of the hospital infrastructure. For the former, it is well known that overweight and obesity are a substantial public health issue in Mexico, which ranks worldwide among the highest in obesity rate (Stevens et al, 2008;Pérez-Salgado et al, 2012;Barquera et al, 2013;DiBonaventura et al, 2018;OECD, 2019b). According to the OECD, 72.5% of the population above 15 years old are overweight in Mexico, with at least 15% reaching the category of obese (OECD, 2019b).…”
Section: Introductionmentioning
confidence: 99%